HUBUNGAN KARAKTERISTIK DENGAN PERILAKU IBU NIFAS DALAM PENCEGAHAN INFEKSI LUKA PERINEUM DI RS ROEMANI MUHAMMADIYAH SEMARANG - Siti Nurjanah; Dewi Puspitaningrum; Rias Ismawati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background : Maternal Mortality Rate, in Indonesian is caused by infection. Infection case about 2,76% which bases maternal death. One of infection in postpartum phase is the infection which is caused pathogen bacteria comes in the way and causes infection if the prevention is not good.Objective : the objective of this research is to know the correlation between characteristic and external or internal attitude of postpartum mother in preventing perineum infection injury at Roemani Muhammadiyah Hospital, Semarang. Method : this research is  correlation analitical research with research approach used 40 postpartum mothers who were 20 primipara and 20 multipara at  Roemani Muhammadiyah Hospital, Semarang, who were taken by quota sampling.Instrument used was quitioner and observation. The data analysis used chi-square test. Result : Based on the result of the research that most of reproduction age about 31 peoples, last education about 18 people in average, jobless respondence about 25 people. The result of chi-square test with p<0,005 , showed that there was significant correlation between characteristic and attitude. At age characteristic with external or internal attitude there was no correlation at all. At education variabel with external attitude there was correlation with p=0,003, and adecation with internal attitude there was no correlation at all. At job characteristic with external or internal attitude there was no correlation at all. At parity characteristic with external or internal attitude there was no correlation at all. Conclusion : there was correlation between education and external attitude ofpostpartum mother in preventing perineum infection injury. External factor which showed negative attitude in this research, most of them had not consumed food and tonic made of medical herbs, internal attitude was that they didn’t wash hands before cleaning vagina.Keywords : Characteristic, infection prevention, perineum injury